Scale-up biopolymer-chelated fabrication of cobalt nanoparticles encapsulated in N-enriched graphene shells for biofuel upgrade with formic acid. Issue 17 (12th August 2019) - Zhou, Shenghui; Dai, Fanglin; Dang, Chao; Wang, Ming; Liu, Detao; Lu, Fachuang; Qi, Haisong
Abstract : Carboxymethyl cellulose-derived Co nanocatalysts sheathed in N-doped graphene exhibited an excellent catalytic activity for base-free transfer hydrodeoxygenation of vanillin with formic acid. Abstract : Exploring both high-performance catalytic materials from non-edible lignocellulosic biomass and selective hydrodeoxygenation of bioderived molecules will enable value-added utilization of renewable feedstocks to replace rapidly diminishing fossil resources. Herein, we developed a scale-up and sustainable method to fabricate gram-quantities of highly dispersed cobalt nanocatalysts sheathed in multilayered N-doped graphene (Co@NG) by using a biomacromolecule carboxymethyl cellulose (CMC) as a raw material. The ionic gelation of CMC, urea and Co 2+ ions leads to uniform dispersion and chelation of different species, consequently resulting in the formation of highly distributed Co nanoparticles (NPs) (10.91 nm) with N-enriched graphene shells in the solid-state thermolysis process. The usage of urea as a non-corrosive activation agent can introduce a porous belt-like nanostructure and abundant doped nitrogen. Among all the prepared catalysts in this work, the optimized Co@NG-6 with the largest specific surface area (627 m 2 g −1 ), the most and strongest basic sites, and the highest proportion of pyridinic-N (37.6%) and mesopores exhibited excellent catalytic activity (99% yield of 2-methoxy- p -cresol) for base-free transfer hydrodeoxygenation (THD) of vanillin using bioderived formic acid (FA) as a H source at 160 °C for 6 h. The poisoning tests and electron paramagnetic resonance (EPR) spectra verified that the strong interaction between N atoms and encapsulated Co NPs provided synergistic effects, which were essential for the outstanding catalytic performance of Co@NG-6. The deuterium kinetic isotope effect study clearly demonstrated that the formation of Co-H − via β-hydride elimination and protonation was the rate-determining step, and protic N–H + and hydridic Co-H − were considered to be active intermediate species in the THD reaction. Furthermore, Co@NG-6 was highly stable for recycling owing to the graphene shells preventing Co NPs from corrosion and aggregation.